1988
DOI: 10.1002/ajmg.1320300138
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of stimulant medication in children with the fragile X syndrome

Abstract: Attentional deficits and hyperactivity frequently are major problems for fra(X) boys. This study evaluated the effectiveness of 2 stimulant medications, methylphenidate and dextroamphetamine compared to placebo in 15 children (13 males, 2 females) with the fra(X) syndrome. A double-blind crossover design was used with outcome measures which included parent and teacher behavior checklists, a controlled observation period, continuous performance tasks and an actometer measure of movement. When the children were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 27 publications
5
76
1
Order By: Relevance
“…Psychostimulants are the most often prescribed psychoactive medication to treat FXS [730], with initial randomized controlled trial data of response to methylphenidate and dextroamphetamine suggesting moderate response rates on attention and social skills [731]. Preliminary studies of aripiprazole in FXS have also found evidence for an improvement in clinical symptoms and irritability [732,733].…”
Section: Reviewmentioning
confidence: 99%
“…Psychostimulants are the most often prescribed psychoactive medication to treat FXS [730], with initial randomized controlled trial data of response to methylphenidate and dextroamphetamine suggesting moderate response rates on attention and social skills [731]. Preliminary studies of aripiprazole in FXS have also found evidence for an improvement in clinical symptoms and irritability [732,733].…”
Section: Reviewmentioning
confidence: 99%
“…Parents and professionals often report that challenging behaviors are their greatest concern regarding their child with FXS [Hagerman, 1996b;Hatton et al, 2000]. Perhaps one of the most striking indicators of these problems is the extensive use of medications with FXS children, sometimes at very young ages [Tranfaglia, 1995;Hagerman, 1996a].In estimating the effectiveness of stimulants, one study reported that attention and sociability were improved in boys with FXS on a trial of methylphenidate [Hagerman et al, 1988]. Interestingly, the effectiveness of stimulants may be related to intellectual ability and, more speci®cally, may not be effective in children with severe mental retardation.…”
mentioning
confidence: 97%
“…While an early controlled trial of stimulant medication for ADHD symptoms in fragile X children showed modest benefit [Hagerman et al, 1988], the study suffered from a number of methodological shortcomings, including a small number of subjects, the use of two different study drugs, and a very brief duration of treatment. Even with a brief exposure to the active drug, significant psychiatric side effects were seen in some subjects.…”
Section: Attention Deficit and Hyperactivitymentioning
confidence: 99%